A cohesive interface crack model for the matrix–textile debonding in FRCM composites. (20th May 2016) - Carozzi, Francesca Giulia; Colombi, Pierluigi; Fava, Giulia; Poggi, Carlo
Abstract: Existing masonry structures often need to be strengthened or repaired. Among non-traditional retrofitting techniques, Fibre Reinforced Cementitious Matrix (FRCM) materials are becoming more and more interesting, especially for the reinforcement of historical buildings. The bond strength of the FRCM reinforcement is one of the key factors affecting the behaviour of the reinforced member and failure mode mostly involves the failure of the textile/mortar interface. Based on experimental results on single lap pull–push shear tests on FRCM materials bonded to masonry blocks, a tri-linear bond–displacement behaviour at the textile–mortar interface is proposed. The last phase of the bond–slip law is characterized by a constant shear stress in order to model the friction phenomena between the matrix and the textile observed in the experimental tests. Analytical expressions for the load–displacement response and interfacial shear stress distribution at different loading stages are derived taking into account the effects of the friction phenomena. The model is discussed in detail and the analytical results are compared to experimental outcomes. Finally, a parametric analysis is performed to highlight the effect of bond length, cohesive bond–slip law parameters and friction on the load–displacement response.